2011
DOI: 10.1111/j.1754-9485.2011.02309.x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging characteristics of extrapulmonary tuberculosis lesions on dual time point imaging (DTPI) of FDG PET/CT

Abstract: Our study demonstrates that early whole body PET/CT imaging may be sufficient for the detection of the EPTB lesions and DTPI of PET/CT may also not be a useful technique in differentiating between EPTB and non-EPTB lesions. However, our findings are based on a limited number of patients, and therefore, further investigations in larger series of patients are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 22 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…In summary, we have provided evidence that the spectrum of clinically defined LTBI, specifically that associated with inflammation detected by PET CT and the presence of extrapulmonary disease, is associated with reactivation risk. It is likely that this occurs in humans with LTBI and similar lung lesions have been described in LTBI humans by PET CT [ 16 , 23 25 ]. Importantly, this is the first assay that can functionally distinguish those at high and low risk for reactivation induced by TNF neutralization.…”
Section: Discussionmentioning
confidence: 76%
“…In summary, we have provided evidence that the spectrum of clinically defined LTBI, specifically that associated with inflammation detected by PET CT and the presence of extrapulmonary disease, is associated with reactivation risk. It is likely that this occurs in humans with LTBI and similar lung lesions have been described in LTBI humans by PET CT [ 16 , 23 25 ]. Importantly, this is the first assay that can functionally distinguish those at high and low risk for reactivation induced by TNF neutralization.…”
Section: Discussionmentioning
confidence: 76%
“…FDG uptake in inflammatory/infectious tissues was reported to reach its peak in about 60 min after the time of injection, but then it gradually decreased with time. Conversely, malignant lesions have been shown to keep increasing the FDG uptake up to several hours (34,35). However, Razak et al (35) suggested in their study that DTPI of PET/CT may not be a useful technique in differentiating between EPTB and non-EPTB lesions, so the value of DTP FDG PET/CT imaging remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…[14] A study undertaken to evaluate the diagnostic value of dual time point imaging (DTPI) of 18F-FDG PET/CT for detecting the infective lesions in patients with extrapulmonary TB revealed that early whole body PET/CT imaging may be sufficient for the detection of the EPTB lesions and DTPI of PET/CT may also not be a useful technique in differentiating between EPTB and non-EPTB lesions. [15]…”
Section: Discussionmentioning
confidence: 99%